Forest Management Certification System: a Working Plan's Perspective - Jha, Arvind Kumar (Indian Forester, 2004)
The need to institutionalize certification system in Forest Management, even though it may require some additional expenditure, is esential not only to ensure the sustenance of the desired quality of forests but also to secure the future of forestry in our country. As the first step, the principles, criteria and indicators should be woven into the existing system of working plan preparation, implementation, and its monitoring through control forms duly buttressed by inclusion of certification parameters with the simultaneous institution of an independent agency for performing the certification job.